Value of neutrophil-to-lymphocyte ratio for diagnosing sarcopenia in patients undergoing maintenance hemodialysis and efficacy of Baduanjin exercise combined with nutritional support - Wang, Jun; Xu, Mei-chang; Huang, Li-juan; Li, Bei; Yang, Lei; Deng, Xu (Frontiers in Neurology, 2023)
Objective To investigate the value of neutrophil-to-lymphocyte ratio (NLR) for diagnosing sarcopenia in patients undergoing maintenance hemodialysis (MHD) and efficacy of Baduanjin exercise combined with nutritional support on MHD patients with sarcopenia. Methods A total of 220 patients undergoing MHD in MHD centers were selected, among which 84 had occurred with sarcopenia confirmed by measurements from the Asian Working Group for Sarcopenia. Data were collected for analyzing the influencing factors that lead to the onset of sarcopenia in MHD patients with the use of one-way analysis of variance and multivariate logistic regression. The role of NLR in the diagnosis of sarcopenia was explored, and its correlation with relevant diagnostic measurement performance such as grip strength, gait speed and skeletal muscle mass index was analyzed. In the end, some 74 patients with sarcopenia that qualify for further intervention and observation standards were divided into observation group (Baduanjin exercise plus nutritional support) and control group (nutritional support only), which were both intervened for 12 weeks. A total of 68 patients finished all interventions, with 33 patients in the observation group and 35 in the control group. The grip strength, gait speed, skeletal muscle mass index as well as the NLR were compared between the two groups. Results With the employment of multivariate logistic regression analysis, it was found that age, hemodialysis duration and NLR were risk factors for the onset of sarcopenia in MHD patients (P < 0.05). The area under ROC curve for NLR of MHD patients with sarcopenia was 0.695, and NLR was negatively correlated with a biochemical indicator—human blood albumin (P < 0.05). NLR was also negatively correlated with patient's grip strength, gait speed and skeletal muscle mass index, with the same correlation found in sarcopenia patients (all P < 0.05). After intervention, patient's grip strength and gait speed were both higher, and the NLR lower in the observation group than those in the control group (P < 0.05). Conclusion The occurrence of sarcopenia in MHD patients is associated with patient's age, hemodialysis duration and NLR. Therefore, it has been concluded that NLR has certain values in the diagnosis of sarcopenia in patients undergoing MHD. Moreover, the muscular strength can be enhanced and inflammation decreased in sarcopenia patients through nutritional support and physical exercise, i.e., Bajinduan exercise.